2017
DOI: 10.1038/s41598-017-04388-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of plasma membrane lipid domains to red blood cell (re)shaping

Abstract: Although lipid domains have been evidenced in several living cell plasma membranes, their roles remain largely unclear. We here investigated whether they could contribute to function-associated cell (re)shaping. To address this question, we used erythrocytes as cellular model since they (i) exhibit a specific biconcave shape, allowing for reversible deformation in blood circulation, which is lost by membrane vesiculation upon aging; and (ii) display at their outer plasma membrane leaflet two types of submicrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 45 publications
5
83
0
2
Order By: Relevance
“…Regarding lipid domain contribution to RBC reshaping, we have previously shown that the first population of domains, i.e. those mostly enriched in chol, gather in increased curvature areas upon RBC deformation [29]. Here, we provide experimental evidence for the differential contribution of the two other populations of lipid domains in RBC calcium exchanges.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…Regarding lipid domain contribution to RBC reshaping, we have previously shown that the first population of domains, i.e. those mostly enriched in chol, gather in increased curvature areas upon RBC deformation [29]. Here, we provide experimental evidence for the differential contribution of the two other populations of lipid domains in RBC calcium exchanges.…”
Section: Introductionmentioning
confidence: 51%
“…2A). This technique allowed to observe alternating regions of high curvature (HC) at the edges of the RBCs and of low curvature (LC) at the center of the cell [29]. We showed that PC-and GM1-enriched domains were preferentially associated with the LC areas of the RBC, like SM-enriched domains (green, blue and orange arrowheads, Fig.…”
Section: Statistical Analysesmentioning
confidence: 92%
See 3 more Smart Citations